Occupational exposure to asbestos and risk of cholangiocarcinoma: A population-based case-control study in four Nordic countries - Farioli, Andrea; Straif, Kurt; Brandi, Giovanni; Curti, Stefania; Kjærheim, Kristina; Martinsen, Jan Ivar; Sparen, Pär; Tryggvadottir, Laufey; Weiderpass, Elisabete; Biasco, Guido; Violante, Francesco Saverio; Mattioli, Stefano; et al. (Occupational and Environmental Medicine, 2017)
Objectives To assess the association between occupational exposure to asbestos and the risk of cholangiocarcinoma (CC). Methods We conducted a case–control study nested in the Nordic Occupational Cancer (NOCCA) cohort. We studied 1458 intrahepatic CC (ICC) and 3972 extrahepatic CC (ECC) cases occurring among subjects born in 1920 or later in Finland, Iceland, Norway and Sweden. Each case was individually matched by birth year, gender and country to five population controls. The cumulative exposure to asbestos (measured in fibres (f)/ ml × years) was assessed by applying the NOCCA jobexposure matrix to data on occupations collected during national population censuses (conducted in 1960, 1970, 1980/81 and 1990). Odds ratios (OR) and 95% CI were estimated using conditional logistic regression models adjusted by printing industry work. Results We observed an increasing risk of ICC with cumulative exposure to asbestos: never exposed, OR 1.0 (reference category); 0.1–4.9 f/mL × years, OR 1.1 (95% CI 0.9 to 1.3); 5.0–9.9 f/mL × years, OR 1.3 (95% CI 0.9 to 2.1); 10.0–14.9 f/mL × years, OR 1.6 (95% CI 1.0 to 2.5); ≥15.0 f/mL × years, OR 1.7 (95% CI 1.1 to 2.6). We did not observe an association between cumulative asbestos exposure and ECC. Conclusions Our study provides evidence that exposure to asbestos might be a risk factor for ICC. Our findings also suggest that the association between ECC and asbestos is null or weaker than that observed for ICC. Further studies based on large industrial cohorts of asbestos workers and possibly accounting for personal characteristics and clinical history are needed.